Somatic Testing on Gynecological Cancers Improve the Identification of Lynch Syndrome. Issue 7 (1st September 2017) - Carnevali, Ileana; Libera, Laura; Chiaravalli, Annamaria; Sahnane, Nora; Furlan, Daniela; Viel, Alessandra; Cini, Giulia; Cimetti, Laura; Rossi, Thomas; Formenti, Giorgio; Ghezzi, Fabio; Riva, Cristina; et al.
Abstract : Objective: Recent data from the literature indicate gynecological cancers (GCs) as sentinel cancers for a diagnosis of Lynch syndrome (LS). Clinical approaches to identifying LS have low sensitivity, whereas somatic tests on GCs may be a more sensitive and cost-effective strategy. Methods: A series of 78 GCs belonging to 74 patients sent to the Genetic Counselling Service were investigated using microsatellite instability, immunohistochemical expression of mismatch repair (MMR) genes, and MLH1 promoter methylation. Results: The presence of microsatellite instability was observed in 67.5% of GCs, and the absence of immunohistochemical expression of at least 1 of the 4 MMR proteins was observed in 71.4% of GCs, showing 96.1% concordance between the methods. Methylation analysis using methylation specific multiplex ligation-dependent probe amplification performed on 35 samples revealed MLH1 promoter hypermethylation in 18 cases (54%). Molecular analysis identified 36 LS carriers of MMR variants (27 pathogenetic and 9 variants of uncertain significance), and, interestingly, 3 LS patients had MLH1 methylated GC. With regard to histological features, LS-related GCs included endocervical cancers and also histological types different from the endometrioid cancers. The presence of peritumoral lymphocytes in GCs was statistically associated with LS tumors. Conclusions: Somatic analysis is a useful strategy to distinguish sporadic from LS GC. Our data allow the identification of a subset of LS patients otherwise unrecognized on the basis of clinical or family history alone. In addition, our results indicate that some clinicopathological features including age of GC diagnosis; presence of peritumoral lymphocytes; isthmic, endocervical sites, and body mass index value could be useful criteria to select patients for genetic counseling.